2011
DOI: 10.4049/jimmunol.1001881
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Regulation of GATA-3 and Th2 Cytokine Gene Expression by the RNA-Binding Protein HuR

Abstract: The posttranscriptional mechanisms whereby RNA-binding proteins (RBPs) regulate T cell differentiation remain unclear. RBPs can coordinately regulate the expression of functionally related genes via binding to shared regulatory sequences, such as the Adenylate-Uridylate-Rich Elements (ARE) present in mRNA’s 3′ untranslated region (UTR). The RBP HuR posttranscriptionally regulates IL-4, IL-13 and other Th2-cell-restricted transcripts. We hypothesized that the ARE-bearing GATA-3 gene, a critical regulator of Th2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 61 publications
2
50
0
Order By: Relevance
“…HuR has been reported to stabilize transcripts of multiple proinflammatory cytokines including, but not limited to, cyclooxygenase 2, TNF-a, vascular endothelial growth factor, and IL-13 (23)(24)(25). In this study, we report that HuR directly binds to IL-17 39 UTR mRNA and stabilizes its transcript, which in turn results in increases in both IL-17 mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…HuR has been reported to stabilize transcripts of multiple proinflammatory cytokines including, but not limited to, cyclooxygenase 2, TNF-a, vascular endothelial growth factor, and IL-13 (23)(24)(25). In this study, we report that HuR directly binds to IL-17 39 UTR mRNA and stabilizes its transcript, which in turn results in increases in both IL-17 mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 64%
“…The RBP HuR positively regulates stability of many target mRNAs via binding AREs present in the 39 UTR, including inflammatory cytokines such as IL-4, IL-13, and TNF-a (23)(24)(25)(26). In this study, we demonstrated that IL-17 mRNA and protein levels in polarized Th17 cells from HuR conditional knockout (KO) mice are reduced compared with wild-type (WT) Th17 cells.…”
Section: D4mentioning
confidence: 70%
See 2 more Smart Citations
“…The molecular events leading to T cell activation must be tightly controlled to prevent the development of disease states, such as autoimmunity or malignancy (2)(3)(4), and it is becoming increasingly clear that posttranscriptional gene regulation at the level of mRNA degradation is critical for normal cellular activation, proliferation, and immune effector function (5,6). Indeed, over half of the gene expression changes in early T cell activation are a result of changes in mRNA half-life (7).…”
mentioning
confidence: 99%